Investigation on the mechanical and physical properties of TPU/PVC blend as potential material of bedpan. Issue 1 (June 2016) - Hakim, M.I; Shahnaz, S. S. B.; Luqman, M.; Anis, N.I.; Shuhaida, Y.; Zaharah, S.A.; Baidi, M.B.; Yu, C.W.; Kathiresan, V. S.
Abstract: The purpose of this study is to determine the impact properties, chemical resistance and morphology of TPU/PVC blend in order to be used as potential material to fabricate bedpan. TPU and incorporation of PVC in TPU was done by melt-mixing method. The blends of TPU/PVC from melt mixing were then undergoing hot press compression moulding to produce sample with 3mm thickness. The blend sample was subjected to drop weight impact test, chemical resistance test and SEM test. Results from impact test showed that 30/70 TPU/PVC has recorded the maximum velocity impacted by 6 J of 1.8 m/s at 97ms while 50/50 TPU/PVC has the highest force (impact strength) of 0.95kN compared with other samples. The result also found that 50/50 TPU/PVC blend has lowest weight change, indicated that the blend has good resistance toward NaOH. HCl has a stronger effect on TPU/PVC blend compared to NaOH for all blend composition where 10/90 TPU/PVC showed highest resistance towards HCl. The micrograph shows that 50/50 TPU/PVC exhibited both smooth surface, indicating the brittleness of PVC and rough and the plasticity fractured surface, indicating the ductility of TPU features.